(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Research aims to find knowledge of the environmental education dimensions for sustainable development included in the science book for the second grade of primary school, and the descriptive analytical method was used, to analyze the content of the science book for the second grade of primary school, 1st Edition / 2017. for the year (2018/2019) of the dimensions of environmental education for sustainable development after excluding the chapter questions, introduction, and list of contents from the analysis. The research tool included building a list of environmental education dimensions for sustainable development that should be provided in the science book in light of which the book’s analysis process could be completed.The list included (17) sub-cases distributed among (5) major issues related to the environmental dimensions.The researcher approved the apparent honesty, and it was presented to a group of arbitrators, and the agreement was 80%, and thus it is considered valid and usable. The explicit idea as the unit of frequency analysis is adopted as the unit of census.The researcher presented the sample of the analyzed material to a number of arbitrators, and they unanimously agreed on the validity of the analysis process, which contained the subject of the members in the human body from chapter one, included heart, lungs and stomach from the science book for the second grade of primary school.The researchers used two types of analysis consistency:1- Agreement over time.2- Agreement between analysts. They used external analysts with experience in the analysis process, and to calculate the stability, a sample was chosen from the analyzed material representing 20% ​​of the total content of (33) pages represented in the first unit / the human body and health / chapters 1 and 2. The stability coefficients were from the standard, and the researchers used frequencies, percentage, and the Holste equation statistically. It was found through the results that the environmental dimension came with (7) frequencies and a percentage of 13.73% of the total number of (51) frequencies. The book received (51) frequencies distributed to the (3) main issues, the issue of human body and his health In first place (17) frequency with a percentage of 33.3333%, followed by the water environment in second place with (13) frequency and a percentage of 25.4901%, the percentage of land with (11) frequency and a percentage of 21.5686% The material and its states got (8) frequencies , with a percentage of 13.7254%. As for the Earth and the universe, it did not get many frequencies, and it was (3) frequencies and a percentage of 5.8823%.This indicates an interest in aspects and neglect of others, which makes it necessary to pay attention to neglected aspects and include them in science books